Analysis of Coaching and Supervision Results for Bandung City Hospitals by the Bandung City Health Office in 2024 - Rahayu, Awalia; Susanti, Ai Susi (CV. Science Tech Group, 2024)
This study aims to determine the percentage increase in hospital facilities in Bandung from 2023 to May 2024 implemented by the Bandung City Health Office. The research method used is a qualitative method with a descriptive approach. The data collection technique used by researchers is a Focus Group Discussion of the coaching and supervision activities of Bandung City hospitals by the Bandung City Health Office 2024. The results showed that in 2023, the average number of facilities in 43 hospitals was 61.7 while 78.6. So there is an increase in the average value of hospital facilities in Bandung city from 2023 to 2024 this May by 16.93%. In addition, the infrastructure in hospitals from 2023 to 2024 has also increased. In 2023 itself, the average number of hospital infrastructure in Bandung city was 67.5 then increased to 80.9 in May 2024. So there was an increase in the percentage of hospital infrastructure in Bandung from 2023 to May 2024 by 13.4%. Furthermore, regarding medical devices, the increase that occurred in the results of the completeness of medical devices in Bandung city hospitals from 2023 was 12.1%. This can be seen from the average number of medical devices in 2023 Bandung City hospitals of 53.8 and 2024 until this May 65.9 so the implementation of hospital supervision and guidance activities has a significant impact on the process of developing hospital facilities in Bandung City.